Synthesis, molecular docking and in vitro antimicrobial studies of novel pyrazole analogues of curcumin - Kumar D.; Harish B.G.; Gangwar M.; Kumar M.; Kumar D.; Tilak R.; Nath G.; Kumar A.; Singh S.K. (My University, 2025)
A series of pyrazole analogues of curcumin were synthesized and investigated for in vitro and in silico antimicrobial activity. The structures of newly synthesized compounds were ascertained on the basis of their analytical and spectral profiles. The compounds were subjected to molecular docking studies for the inhibition of the enzyme glucosamine-6- phosphate synthase [GlcN-6-P]. The autodock program 4.2 was employed to perform automated molecular docking. The docking study was performed on two different active sites of the enzyme reside with the amino acid series Cys1, Arg73, Thr76, His77, Asn98, Gly99, Ile100 and Gly301, Thr302, Ser303, Ser347, Gln348, Ser349, Thr352, Lys485, Ala602, Val605 respectively. Among the thirteen molecules taken for docking studies, compounds cp10, cp11 and cp12 showed minimum docking energy and inhibition constant and may be considered as good inhibitor of GlcN-6-P synthase. © 2014 Bentham Science Publishers.